Analysis of Hedging Strategies for Optimal Risk Management in Islamic Banking - Adelisa, Nur Rahma; Amelia, Reski; Nabila, Ila; Arsyad, Kamaruddin; Kamil, Muh. Ahsan (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to analyze the implementation of hedging strategies as an optimal risk management approach in Islamic banking institutions in Indonesia. Facing global economic volatility and currency fluctuations, Islamic banks are required to adopt risk management policies that are not only financially effective but also compliant with Sharia principles. This research employs a qualitative approach using library research methods by reviewing academic literature, DSN-MUI fatwas. The findings reveal that internal factors such as liquidity, leverage, firm size, and financial condition significantly influence the decision to apply hedging within Islamic banks. Meanwhile, external factors—including government policies, regulatory changes, and global market dynamics—further reinforce the necessity of risk management strategies grounded in justice and sustainability. The implementation of Sharia-based hedging is proven to enhance financial stability, strengthen public trust, and improve the competitiveness of the Islamic financial industry at both national and international levels. This study contributes theoretically and practically to the development of innovative, ethical, and sustainable Sharia-compliant financial instruments